Diseases from the wild: interview with Hung Nguyen - Hung Nguyen-Viet (International Livestock Research Institute, 2020)
Dr Hung Nguyen, regional representative for ILRI East and Southeast Asia, is interviewed by Vietnam's VTC14 station on 'Diseases from the wild.' Dr Nguyen talks about how zoonotic diseases can pass from animals to humans, and makes recommendations for how to prevent pandemics like COVID-19.